(3 + c) (9 - 3 c + c^2)
c^3+27 addition of cubes (c+3)(c^2+3c+9) Am I reading the problem wrong?
No, but your answer is wrong. close, but wrong.
right, its the formula. i never can rember the correct formula. (c+3)(c2-3c+9) i think.
Ding!... I guess I'd forgotten that there's a formula for disemboweling a cubic equation. I played the "guess the first term" game...
I suspect that you were supposed to memorize the factorizations of the sum of cubes, difference of cubes, difference of squares, and perfect square trinomials. If you memorize these, you will save yourself a great deal of trouble. (a^3^ + b^3^) = (a^3^ - b^3^) = (a^2^ - b^2^) = (a^2^ + 2ab + b^2^) = (a^2^ - 2ab + b^2^) =
Another clue is C cubed = -27
Perhaps start by thinking of it as a disguised quadratic instead of a cubic equation?